2022
DOI: 10.3390/microorganisms10112190
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Phenotyping in Inflammatory Bowel Disease: Search for Biomarker Algorithms in the Transkingdom Interactions Context

Abstract: Inflammatory bowel disease (IBD) is the most common form of intestinal inflammation associated with a dysregulated immune system response to the commensal microbiota in a genetically susceptible host. IBD includes ulcerative colitis (UC) and Crohn’s disease (CD), both of which are remarkably heterogeneous in their clinical presentation and response to treatment. This translates into a notable diagnostic challenge, especially in underdeveloped countries where IBD is on the rise and access to diagnosis or treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Patients with IBD often have decreased hemoglobin levels due to intestinal bleeding and anemia, which are indicative of inflammation and tissue damage [ 46 , 47 ]. Research has demonstrated that lower hemoglobin and hematocrit levels can signify a quicker advancement of complex CD behaviors or CD-related surgery [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IBD often have decreased hemoglobin levels due to intestinal bleeding and anemia, which are indicative of inflammation and tissue damage [ 46 , 47 ]. Research has demonstrated that lower hemoglobin and hematocrit levels can signify a quicker advancement of complex CD behaviors or CD-related surgery [ 48 ].…”
Section: Discussionmentioning
confidence: 99%